Variation through the first half of lactation in bulk tank somatic cell counts for Murciano-Granadina goats - Luengo C.; Torres A.; Contreras A.; Sánchez A. (Production systems and product quality in sheep and goats, 2001)
This study reports on the changes in bulk tank SCC for eight goat herds through the first half of two lactations (1997-98 and 1998-99). For each lactation, bulk tank SCC were determined daily for five consecutive months (November-March). Global geometric means for both lactations were 973,000 cell-ml (1997-98) and 719,000 cell-ml (1998-99), an important improvement on the SCC of the herds. SCC profiles for the eight herds were similar. The mastitis control programme implemented at the end of the first lactation resulted in reduced SCC for all eight herds. During both lactations bulk tank SCC for all herds were below the suggested limit of 1,500,000 cell-ml proposed for goats and ewes by the scientific committee of the International Symposium 'Somatic Cells and Milk of Small Ruminants' of Bella in 1994. Prevalence of subclinical mastitis, level of milk production and number of primiparous goats were important factors contributing to increased bulk tank SCC.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)